Could circulating biomarkers of nitrosative stress and protein glycoxidation be useful in patients with gastric cancer? - Dorf, Justyna; Pryczynicz, Anna; Matowicka-Karna, Joanna; Zaręba, Konrad; Żukowski, Piotr; Zalewska, Anna; Maciejczyk, Mateusz (Frontiers in Oncology, 2023)
Background Nitrosative stress leads to protein glycoxidation, but both processes may be strongly related to the cancer development. Therefore, the aim of this study was to assess the nitrosative stress and protein glycoxidation products in patients with gastric cancer in comparison with healthy controls. We are also the first to evaluate the diagnostic utility of nitrosative stress and protein glycoxidation markers in gastric cancer patients in respect to histopathological classifications (TNM, Lauren’s and Goseki’s classification) and histopathological parameters such as histological type, histological differentiation grade, presence of vascular or neural invasion, desmoplasia and Helicobacter pylori infection. Methods The study included 50 patients with gastric cancer and 50 healthy controls matched for sex and age. Nitrosative stress parameters and protein glycoxidation products were measured colorimetrically/fluorometrically in plasma or serum samples. Student’s t-test or Mann-Whitney U-test were used for statistical analysis. Results NO, S-nitrosothiols, nitrotyrosine, kynurenine, N-formylkynurenine, dityrosine, AGE and Amadori products were significantly increased whereas tryptophan fluorescence was decreased in patients with gastric cancer compared to the healthy control. Nitrosative stress and glycoxidation products may be useful in diagnosis of gastric cancer because they differentiate patients with gastric cancer from healthy individuals with high sensitivity and specificity. Some of the determined parameters are characterised by high AUC value in differentiation of GC patients according to the histopathological parameters. Conclusions Gastric cancer is associated with enhanced circulating nitrosative stress and protein glycation. Although further research on a tissue model is needed, plasma/serum biomarkers may be dependent on tumour size, histological type, tumour invasion depth, presence of lymph node and distant metastasis, vascular and neural invasion and Helicobacter pylori infection. Thus, circulating biomarkers of nitrosative stress/protein glycoxidation may have potential diagnostic significance in gastric cancer patients.